2013
DOI: 10.1186/1471-2407-13-334
|View full text |Cite
|
Sign up to set email alerts
|

Implication from thyroid function decreasing during chemotherapy in breast cancer patients: chemosensitization role of triiodothyronine

Abstract: BackgroundThyroid hormones have been shown to regulate breast cancer cells growth, the absence or reduction of thyroid hormones in cells could provoke a proliferation arrest in G0-G1 or weak mitochondrial activity, which makes cells insensitive to therapies for cancers through transforming into low metabolism status. This biological phenomenon may help explain why treatment efficacy and prognosis vary among breast cancer patients having hypothyroid, hyperthyroid and normal function. Nevertheless, the abnormal … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
50
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(52 citation statements)
references
References 33 publications
2
50
0
Order By: Relevance
“…Judging from recent observations in various types of malignant tumour disease, this line of research may also lead to new strategies for treatment of breast cancer [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Judging from recent observations in various types of malignant tumour disease, this line of research may also lead to new strategies for treatment of breast cancer [32, 33]. …”
Section: Discussionmentioning
confidence: 99%
“…Some epidemiological studies have reported increased risks associated with hypothyroidism (8,9), hyperthyroidism (10,11,12), goiter (13) and thyroid autoimmune diseases (14,15), while others have found no association (9,16,17,18). Only four studies employed a cohort design (9,11,12,15); in case-control studies, reverse causation is a plausible competing explanation since breast cancer or its treatment may affect thyroid hormone levels (19). Moreover, some studies have not distinguished between hypothyroidism and hyperthyroidism, despite their contrasting hormonal profiles (13,16,17).…”
Section: Introductionmentioning
confidence: 99%
“…The presence of thyroid hormone receptor alpha (THRa) has been demonstrated Furthermore, thyroid hormones exert effects on breast cancer cells in vitro (19,20). In accordance, a very recent study has demonstrated the presence of both THRa and THRb in breast cancer cells (21).…”
Section: Discussionmentioning
confidence: 70%